Effects of point source emission heights in WRF-STILT: a step towards exploiting nocturnal observations in models - Maier, Fabian; Gerbig, Christoph; Levin, Ingeborg; Super, Ingrid; Marshall, Julia; Hammer, Samuel (Geoscientific model development, 2021)
Abstract. An appropriate representation of point source emissions in atmospheric transport models is very challenging. In the Stochastic Time Inverted Lagrangian Transport model (STILT), all point source emissions are typically released from the surface, meaning that the actual emission stack height plus subsequent plume rise is not considered. This can lead to erroneous predictions of trace gas concentrations, especially during nighttime when vertical atmospheric mixing is minimal. In this study we use two WRF-STILT model approaches to simulate fossil fuel CO2 (ffCO2) concentrations: (1) the standard “surface source influence (SSI)” approach, and (2) an alternative "volume source influence (VSI)" approach, where nearby point sources release CO2 according to their effective emission height profiles. The comparison with 14C-based measured ffCO2 data from two-week integrated afternoon and nighttime samples collected at Heidelberg, 30 m above ground level, shows that the root-mean-square deviation (RMSD) between modelled and measured ffCO2 is indeed almost twice as high during night (RMSD = 6.3 ppm) compared to the afternoon (RMSD = 3.7 ppm) when using the standard SSI approach. In contrast, the VSI approach leads to a much better performance at nighttime (RMSD = 3.4 ppm), which is similar to its performance during afternoon (RMSD = 3.7 ppm). Representing nearby point source emissions with the VSI approach could, thus, be a first step towards exploiting nocturnal observations in STILT. To further investigate the differences between these two approaches, we conducted a model experiment in which we simulated the ffCO2 contributions from 12 artificial power plants with typical annual emissions of one million tons of CO2 and with distances between 5 and 200 km from the Heidelberg observation site. We find that such a power plant must be more than 50 km away from the observation site in order for the mean modelled ffCO2 concentration difference between the SSI and VSI approach to fall below 0.1 ppm.
Gesehen am 09.03.2021